Some problems of India's economic policy : selected readings on planning, agriculture, and foreign trade - Wadhva, Charan D. (New Delhi : Tata McGraw-Hill Pub. Co., 1977)
This volume is primarily designed for students and researchers of Indian's economic problems at the postgraduate level. Besides stimulating thought on major issues of the economic policy, it should give them an opportunity of getting acquainted with research methodology, thus enabling them to independently analyse the economic problems facing the country and to evaluate the economic policies of the Government.
Includes bibliographical references p. [764]-768.
hza 28/06/2018
Loans
Keywords: Economic policy; India